Public examinations in Tanzania 1926-1976 : a thesis presented in partial fulfillment of the requirements for the degree of Master of Arts in Education at Massey University - Gandye, Paul Peter (Massey University, 1978)
Ever since 1967 when Tanzania adopted the policy of socialism, the problem of examinations has been discussed. Since then some reforms have been introduced in the examination system by (a) the nationalization of the examination system and (b) the introduction of continuous assessment as part and parcel of what constitutes a student's pass or failure. However, despite these changes it is felt that there is still a need for a suitable examination system. The purpose of this study, therefore, was to examine, from an historical perspective the factors which influence an examination system with the view to having an insight into some of the problems connected with examinations. More specifically the study addressed itself to the following questions. (a) what role or roles have public examinations played in Tanzania's education system since 1926? The aim here was to establish why, despite criticisms, public examinations have continued to exist. (b) In the light of experiences elsewhere, what should be the nature and role of examinations given the present educational socio-political and economic conditions of the country? (c) What is more desirable for Tanzania; a public examination, an internal assessment or a combination of both? It has been established that public examinations in Tanzania have largely played the role of selection despite the fact that they have been meant to certify that a candidate has completed a certain phase of education. In this "misuse" lies the source of criticisms that have been levelled against examinations generally. Since in the Tanzanian context the need for selection examinations still exists, it has been recommended that efforts should be made to find better means of selection rather than the present use of traditional examinations whose predictive validity is questionable. In this regard, therefore, it has been recommended to explore the possibility of using aptitude tests. It has also been established that there is a need to improve the efficiency of the present examinations by formulating clear and precise examination objectives derived from clear and precise curricula objectives, Consequently the need for close collaboration between curriculum developers and examiners has been stressed. In the light of experiences in countries such as New Zealand, Australia, England, Russia, Cuba, China and Korea, it seems that Tanzania cannot completely do away with public examinations at this stage. The decision to introduce continuous assessment in the system of examining appears to be a step in the right direction but in order for the system to work successfully it is necessary to familiarise all concerned, especially teachers, with the basic techniques of testing and educational measurements. There is also a need for an efficient system of moderation which seems to be lacking at present. Finally the necessity for constant research into and evaluation of any changes in the examination system with the view to making it a more efficient tool of educational evaluation and development has been emphasised.
Keywords: Examinations -- Tanzania